2014
DOI: 10.1186/1471-244x-14-84
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of dementia: a cross-sectional study of primary care older patients

Abstract: BackgroundThe epidemiologic study of comorbidities of an index health problem represents a methodological challenge. This study cross-sectionally describes and analyzes the comorbidities associated with dementia in older patients and reviews the existing similarities and differences between identified comorbid diseases using the statistical methods most frequently applied in current research.MethodsCross-sectional study of 72,815 patients over 64 seen in 19 Spanish primary care centers during 2008. Chronic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
170
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(188 citation statements)
references
References 34 publications
11
170
0
4
Order By: Relevance
“…The same authors note that even when illness burden is controlled for, the care costs of patients with dementia may be up to 34% higher than those of aged matched controls, with outpatient pharmaceuticals being the key driver of cost difference [20]. A recent Spanish primary care based study found increased rates of Parkinson's disease and cerebrovascular disease, consistent with this dataset, [21] but additionally reported higher rates of thyroid conditions, heart disease, retinal disorder and prostatic hypertrophy. This sample of 3,971 people with dementia was however, considerably smaller than the population reported here.…”
Section: Comparison With Related Worksupporting
confidence: 70%
“…The same authors note that even when illness burden is controlled for, the care costs of patients with dementia may be up to 34% higher than those of aged matched controls, with outpatient pharmaceuticals being the key driver of cost difference [20]. A recent Spanish primary care based study found increased rates of Parkinson's disease and cerebrovascular disease, consistent with this dataset, [21] but additionally reported higher rates of thyroid conditions, heart disease, retinal disorder and prostatic hypertrophy. This sample of 3,971 people with dementia was however, considerably smaller than the population reported here.…”
Section: Comparison With Related Worksupporting
confidence: 70%
“…These included hypertension, diabetes, and other comorbidities such as congestive heart failure, cerebrovascular disease, and cardiac arrhythmia that have been significantly associated with dementia [15]. Anemia is a recognized risk factor as well as above risk factors to develop dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing awareness and use of health services for dementia, it also seems likely that the costs of medical services will increase more rapidly in the coming decades than by 5% annually, that is, by the rate we used in our sensitivity analysis. Third, as people with dementia often suffer from other chronic health conditions, 50 , 51 comorbidities might reduce the accuracy of our estimates of dementia costs. Fourth, data on the proportion of patients with dementia seeking professional care were very limited.…”
Section: Discussionmentioning
confidence: 99%